Analysis of Machines Providing Liquid Fertilizer to the Root System of Orchard and Vine Seedlings (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2023)
In the world, scientific-research works are being conducted aimed at the development of new scientific and technical bases of resource-saving technologies of pouring fertilizer juice between garden rows and the technical means that implement them. In this direction, the development of the structural scheme of the working part that locally pours fertilizer juice between the rows of the garden and the justification of the technological work process, the purposeful scientific research on ensuring resource efficiency in the processes of its interaction with the soil and tree roots conducting research is one of the urgent issues. In this regard, it is necessary to develop multifunctional working parts.